Nutrition Status of Children, Teenagers, and Adults From National Health and Nutrition Surveys in Mexico From 2006 to 2020 - Shamah-Levy, Teresa; Cuevas-Nasu, Lucia; Romero-Martínez, Martín; Gómez-Humaran, Ignacio Méndez; Ávila-Arcos, Marco Antonio; Rivera, Juan A. (Frontiers in Nutrition, 2021)
Background: Population-level health and nutrition surveys provide critical anthropometric data used to monitor trends of the prevalence of undernutrition and overweight in children under five years old, and overweight and obesity in the population over five years of age. Objective: To present Mexican databases publicly available that contain national-level anthropometric data, which allow to monitor nutritional status indicators in the population, such as undernutrition, overweight and obesity. Materials and methods: Comparable anthropometric data was gathered by five Mexican National Health and Nutrition Surveys (in Spanish, ENSANUT). In pre-school-age children, undernutrition status was identified through underweight (Z-score below -2 in weight -for-age), stunting (chronic malnutrition) (Z-score below -2 for length/height-for-age) or wasting (Z-score below -2, for weight-for-length/height); overweight status was defined as a Body Mass Index (BMI, kg/m2) for age over +2. For school-age children and adolescents, a Z-score BMI between +1 and +2 deviations was defined as overweight, and between +2 and +5.5 as obesity. In adults (≥20 years of age), overweight status was classified as a BMI between 25.0 and 29.9, and obesity as ≥30. Results: The anthropometric data presented derives from the databases of five survey years of the Mexican National Health and Nutrition Survey: 2006, 2012, 2016, 2018 and 2020. They include a total of 210,915 subjects with complete anthropometric data (weight, length/height) distributed on five survey moments; subjects were categorized by age group: pre-school-age children (n=25,968), school-age children (n=42,255), adolescents (n=39,275) and adults (n=103,417). Prevalence of malnutrition by indicator was calculated: in pre-school-age children: low height- and weight-for-age, low weight-for-height and overweight; and in school-age children, adolescents and adults, the indicators calculated were overweight and obesity. Conclusions: Results demonstrate the importance of maintaining systematic, reliable and timely national anthropometric data in the population, in order to detect and track trends and to form the basis of nutrition-related public policy.